2021
DOI: 10.1038/s41598-021-02233-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in femoral neck and total hip bone mineral density following hospitalisation for diabetes-related foot ulceration

Abstract: Management of diabetes-related foot ulceration (DFU) includes pressure offloading resulting in a period of reduced activity. The metabolic effects of this are unknown. This study aims to investigate changes in bone mineral density (BMD) and body composition 12 weeks after hospitalisation for DFU. A longitudinal, prospective, observational study of 22 people hospitalised for DFU was conducted. Total body, lumbar spine, hip and forearm BMD, and total lean and fat mass were measured by dual-energy X-ray absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Whilst it is a recognised mode of protection for wound healing, the off-loading of a limb comes with its own health risks. A recent study has demonstrated bilateral reductions in bone mineral density (BMD) of 1.4-2.8% at the femoral neck and total BMD at the hip 12 weeks after hospital admission for DFU (27). The authors of this study concluded that this nding was likely to be related to disuse due to prolonged o oading periods, and elevated levels of serum in ammatory markers.…”
Section: Discussionmentioning
confidence: 80%
“…Whilst it is a recognised mode of protection for wound healing, the off-loading of a limb comes with its own health risks. A recent study has demonstrated bilateral reductions in bone mineral density (BMD) of 1.4-2.8% at the femoral neck and total BMD at the hip 12 weeks after hospital admission for DFU (27). The authors of this study concluded that this nding was likely to be related to disuse due to prolonged o oading periods, and elevated levels of serum in ammatory markers.…”
Section: Discussionmentioning
confidence: 80%
“…Whilst it is a recognised mode of protection for wound healing, the off-loading of a limb comes with its own health risks. A recent study has demonstrated bilateral reductions in bone mineral density (BMD) of 1.4–2.8% at the femoral neck and total BMD at the hip 12 weeks after hospital admission for DFU [ 31 ]. The authors of this study concluded that this finding was likely to be related to disuse due to prolonged offloading periods, and elevated levels of serum inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%